Time and cost associated with utilization of services at mobile health clinics among pregnant women - Nyasule Neke; Antonius Reifferscheid; Barbara Buchberger; Jürgen Wasem (BMC, 2018)
Abstract Background Antenatal care (ANC) is provided for free in Tanzania in all public health facilities. Yet surveys suggested that long distances to the facilities limit women from accessing these services. Mobile health clinics (MHC) were introduced to address this problem; however, little is known about the client cost and time associated with utilizing ANC at MHC and whether these costs deter women from using the provided services. Methods Client-exit interviews were conducted by interviewing 293 pregnant women who visited the MHC in rural Tanzania. Two subgroups were created, one with women who travelled more than 1.5 h to the MHC, and the other with women who travelled within 1.5 h. For each subgroup we estimated the direct cost in US$ and time in hours for utilizing services and they hinder service utilization. The Wilcoxon-Mann-Whitney rank sum test was performed to compare the differences between the estimated mean values in the two groups. Result Total direct cost per visit was: US$2.27 (SD = 0.90) for overall, US$2.29 (SD = 1.03) for those women who travelled less than 1.5 h and US$2.53 (SD = 0.63) for those who travelled more than 1.5 h (p = 0.08). Laboratory and medicine cost accounted for 70 and 16% of the total direct cost and were similar across the groups. Total time cost per visit (in hours) was: 3.75 (SD = 1.83), 2.88 (SD = 1.27) for those women who travelled less than 1.5 h and 5.02 (SD = 1.81) for those who travelled more than 1.5 h (p < 0.01). The major contributor of time cost was waiting time; 1.89 (SD = 1.29) for overall, 1.68 (SD = 1.02) for those women who travelled less than 1.5 h and 2.17 (SD = 1.57) for those who travelled more than 1.5 h (p = 0.07). Participants reported having missed their scheduled visit due to lack of money (15%) and time (9%). Conclusion Women receiving nominally free ANC incur considerable time and direct cost, which may result in an unsteady use of maternal care. Improving availability of essential medicine and supplies at health facilities, as well as focusing on efficient utilization of community health workers may reduce these costs.